Quantifying resilience potentials in construction: pilot evaluation of the resilience assessment grid - Tierra-Arévalo, José Marcelo; Pardo-Ferreira, María Carmen; Arezes, Pedro M.; Rubio-Romero, Juan Carlos (Frontiers in Public Health, 2025)
IntroductionThe construction sector’s entrenched hazards and enduring accident statistics necessitate a paradigm realignment - from rigid, checklist-driven Safety-I models toward a dynamic, resilience-centered Occupational Health and Safety Management (OHSM) ethos. This study endeavored to architect a 36-item questionnaire - rooted in Resilience Assessment Grid (RAG) and integrated within the Occupational Health and Safety Plan (OHSP) - to interrogate and quantify the sector’s resilience capabilities.MethodsAdopting a five-phase development trajectory, commenced with an RAG-aligned draft, secured content validity via the Individual Aggregate Method, iteratively refined items, achieved expert consensus through a multi-round Delphi panel and conducted a pilot implementation on an active construction site. Reliability metrics (Cronbach’s α = 0.914) and user acceptability were appraised using a six-point Likert continuum.ResultsThe instrument exhibited robust psychometric properties and operational viability. Empirical findings revealed a provisional “sometimes” alignment with resilient performance across the four RAG pillars - Respond, Monitor, Learn and Anticipate. Spider-diagram visualizations translated complex data into intuitive insights, pinpointing focal areas for resilience enhancement.ConclusionBy transcending conventional audit paradigms, this RAG-based questionnaire delivers a rigorous, actionable blueprint for embedding adaptive capacities within the OHSP. It empowers industry stakeholders and regulators to transition from reactive safety conventions to a proactive, foresight-driven Safety-II framework, fundamentally advancing OHSM in construction.